Effect of FSH Stimulation with Pluronic® F127 on the Quality of Oocytes Collected by Follicular Aspiration in Bos taurus indicus Heifers - Javier Narváez, Héctor; Villalba Rey , Deicy; Lopes Dias da Costa , Ricardo (Journal of Advanced Veterinary Research, 2023)
In bovine in vitro embryo production (IVP), FSH has been used to improve the quality and developmental capacity of oocytes to reach the blastocyst stage. The objective of this study was to evaluate in Bos taurus indicus heifers the effect of FSH incorporated in Pluronic® F127 on the quality of oocytes collected by follicular aspiration. A total of 30 cyclic Brahman heifers were selected and assigned into one of three experimental groups (control group, FSH-SC and FSH-PF127). Heifers in the FSH-SC group received a single dose of 50 mg FSH subcutaneously and heifers in the FSH-PF127 group were treated with 50 mg FSH incorporated in Pluronic® F127. The rate of viable oocytes was higher for the FSH-PF127 group compared to the control and FSH-SC groups. The administration of a single dose of 50 mg of FSH in Pluronic® F127 influenced the oocyte quality and the rate of viable oocytes of Brahman breed heifers.